Postoperative Critical Care for Adult Cardiac Surgical Patients (Springer International Publishing, 2018)
This text reviews the postoperative management of patients who have undergone cardiac surgical procedures, some of the most common and most complicated forms of surgery. These patients and their management are characterized by complex challenges, while among the factors determining ultimate clinical outcome, postoperative critical care is of major importance. This new and extensively updated edition of Postoperative Critical Care for Cardiac Surgical Patients maintains the general clinical approach in explaining and analyzing the course of clinical care in patients undergoing cardiac surgery, providing the reader with a practical "cookbook" of postoperative intensive care in adult cardiac patients. It has been extensively updated to include the developments in this field during the last few years, from new chapters on postoperative management of renal, gastrointestinal and respiratory systems, postoperative management of infectious and inflammatory complications, and postoperative care of transplant patients and postoperative safety. This book is of critical importance for cardiac surgeons, cardiac anesthesiologists and intensivists, and defines optimal daily practice for adult patients undergoing cardiac surgical procedures.